Leveraging constructivism to apply to systemic reform - Confrey, Jere (NOMAD Nordic Studies in Mathematics Education, 2000)
The question posed for this conference was "what are our current understandings of the theoretical foundations of mathematics education?" To address this question, I first asked myself, "Why it is important to answer such a question?" Is it primarily an issue of philosophical investigation? Or, is it, rather, a call for some clarification about the proliferation of theories in mathematics education and their interrelationships, reexamining each theory in light of multiple theories. This second query interests me, because increasingly as I extend the scope of my research to see constructivism enacted in classrooms and schools, I need broader theoretical constructs. And, I need to reexamine of my own assumptions and their warrant.